Knowledge, attitudes and perceptions of Ngonde chiefs on bonus wife practice at Gweleweta Village in Karonga - Munthali, Chiona, Vincent Kachikwati (Kamuzu University of Health Sciences, 2022)
Mbirigha is a form of polygamy in which a man is given his wife's young sister as a second wife MHRC, (2003). This cultural practice is common between the Ngonde of Karonga. It is done mostly to protect the wealth the family so that it does not spill over to other unrelated families. This practice however, has negative effects on the one who is given as a bonus wife and to the first wife as well. For example human right violation, Psychological trauma and risk for HIV transmission just to mention but a few. The design for the study will be explorative qualitative conducted with a purpose of exploring knowledge, attitudes and perceptions of Ngonde chiefs on bonus wife. This study will utilize the Ngonde Chiefs who are based at Gweleweta village in Karonga district. The study will be conducted at Gweleweta village in Karonga district, northern part of Malawi. This village was chosen because its one of the areas where bonus wife is 1 practiced. The sample size for this study will initially be 10 chiefs however; the actual sample size will be decided by data saturation. The participants will be selected using convenience sampling technique. Data will be collected using an individual in-depth interview guide in which face to face interviews will be conducted. Content analysis will be used to analyze the collected data. Recommendations will be made based on the themes that will emerge.